The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0047-20852006000100004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores associados à sintomatologia depressiva em idosos residentes no Nordeste do Brasil

Abstract: ResumoObjetivo: Analisar a influência de fatores sociodemográficos, de saúde física, capacidade funcional e função cognitiva sobre a sintomatologia depressiva de idosos do município de Santa Cruz, no Rio Grande do Norte. Métodos: Estudo com delineamento transversal de base populacional, incluindo 310 idosos, acima de 60 anos, residentes na zona urbana da cidade, nos quais se aplicou a Escala de Depressão Geriátrica (GDS-15). A análise estatística foi realizada com nível de significância p = 0,05, com cálculo d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1
33

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 17 publications
4
17
1
33
Order By: Relevance
“…Regarding the Brazilian institutionalized elderly, the prevalence of depressive symptoms is equivalent to 49.76%, a result that approaches other studies such as the one by Soares et al, (16) that obtained an extremely high prevalence of 73.7% in institutionalized elderly, as well as the study by Maciel and Guerra, (21) with a prevalence of depressive symptoms of 25.5% for noninstitutionalized elderly.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Regarding the Brazilian institutionalized elderly, the prevalence of depressive symptoms is equivalent to 49.76%, a result that approaches other studies such as the one by Soares et al, (16) that obtained an extremely high prevalence of 73.7% in institutionalized elderly, as well as the study by Maciel and Guerra, (21) with a prevalence of depressive symptoms of 25.5% for noninstitutionalized elderly.…”
Section: Discussionsupporting
confidence: 78%
“…This fact is rarely discussed because in most studies, what is observed are gender issues, education and economic factors, i.e., an increased risk among women of low income and low education. (14,21) The environment of long-stay institutions provides challenges to residents and may favor the development of depressive symptoms. Therefore, the awareness of the diagnosis of depression in the institutional context by the technicians responsible for the care is of fundamental importance.…”
Section: Discussionmentioning
confidence: 99%
“…According to Maciel & Guerra, 31 unfavorable social conditions are reflected in low levels of schooling and income, making the individual more susceptible to mental health problems such as depression. These authors also commented on the high levels of illiteracy in Brazil and ratified the idea of an inefficient social services network, reflected in areas such as housing, culture, income and health.…”
Section: Sleep Characteristicmentioning
confidence: 99%
“…Outro estudo, realizado com 310 idosos residentes no nordeste do Brasil, ressalta a íntima dependência entre depressão e capacidade funcional, afirmando ser a limitação funcional um dos potenciais fatores associados ao aparecimento e ao agravamento dos quadros depressivos na população idosa 16 .…”
Section: Discussionunclassified